Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
We will prove the relation by using the quadratic equation general solution.
How to prove that?
If
[tex]x^4 - x^2 +1 =0[/tex]
Then
[tex]x^2 = \frac{1 \pm \sqrt{(-1)^2 - 4*1*1} }{2} \\\\x^2 = \frac{1 \pm \sqrt{-3} }{2}[/tex]
Now, the other equation is:
[tex](1 + \frac{1}{x^{10}} )*x^5 = -\sqrt{3} \\\\(x^5 + \frac{1}{x^5} ) = -\sqrt{3}\\\\x^{10} + 1 = -\sqrt{3}*x^5[/tex]
Writing this as a quadratic:
[tex](x^5)^2 + \sqrt{3}*x^5 + 1 = 0[/tex]
[tex]x^5 = \frac{-\sqrt{3} \pm \sqrt{(\sqrt{3})^2 - 4*1*1} }{2} \\\\x^5 = \frac{-\sqrt{3} \pm \sqrt{(-1)} }{2}[/tex]
Then we must have:
[tex]( \frac{1 \pm \sqrt{3}i }{2} )^{2.5} = \frac{-\sqrt{3} \pm \sqrt{1}i}{2}\\\\( \frac{1 \pm \sqrt{3}i }{2} )^{5/2} = \frac{-\sqrt{3} \pm \sqrt{1}i}{2}\\\\( \frac{1 \pm \sqrt{3}i }{2} )^{5} = (\frac{-\sqrt{3} \pm \sqrt{1}i}{2})^2[/tex]
Which can be checked with a calculator to be true for both signs (the + and -)
If you want to learn more about quadratic equations:
https://brainly.com/question/1214333
#SPJ1
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.